Containerverkehr der Nordrange - Konzeption eines Planungsmodells für den see- und landseitigen Verkehr. Kollaborativer Ansatz zur ganzheitlichen Analyse der Mengenentwicklungen bis zum Jahr 2015. - Jürgens, Sebastian; Straube, Frank (Deutscher Verkehrs-Verl., 2008)
Dynamik ist das Wort, mit dem sich die derzeitigen wirtschaftlichen Entwicklungen und die Entwicklungen im internationalen, maritimen Containerverkehr gut beschreiben lassen. Der daraus resultierende Kapazitätsbedarf hat in den vergangenen Jahren verstärkt zu Engpässen an den Knotenpunkten der Verkehrsinfrastruktur, wie z. B. Häfen und Schienenterminals geführt. difu

The dynamic augmentation of container transport capacity along the Antwerp-Hamburg axis has, in the past, ended to create bottlenecks with regard to the infrastructure and handling facilities at seaports and in their hinterland. Future capacity-related planning for transport network users, including ship-owners and haulage contractors, is very exacting in that it requires a comprehensive, very detailed and feasible long-term forecast to be drawn up. The research project presented aims to make use of the close cooperation among all the parties involved in order to work their extensive knowledge of market conditions into the trade-specific planning model. This collaboration covers such areas as the completion of a statistical data base by gleaning information from individual companies' records in order to prepare a basic matrix, to focus and calibrate the model, and to validate the results. A discussion of real-life problems and recent achievements in the field of freight transport models is to help determinethe requirements and options for an inter-modal traffic flow forecast for a chosen region. A collaborative approach is favoured. difu
Keywords: Güterverkehr; Wasserverkehr; Verkehrsplanung; Container; Menge; Planungsmodell; Verkehrsprognose; Forschungsprojekt; Verkehrsknoten; Eisenbahn; Hafen; Verkehr; Verkehrsforschung; Schiffsverkehr; Containerverkehr; Transportleistung; Kapazitätsbedarf; Spedition; Reederei; Modal Split; Routenwahl